Effect of pre-operative octenidine nasal ointment and showering on surgical site infections in patients undergoing cardiac surgery. Issue 2 (February 2017) - Reiser, M.; Scherag, A.; Forstner, C.; Brunkhorst, F.M.; Harbarth, S.; Doenst, T.; Pletz, M.W.; Hagel, S.
Summary: Objective: To evaluate the effect of pre-operative octenidine (OCT) decolonization on surgical site infection (SSI) rates. Design: Before-and-after cohort study. Patients: Patients undergoing an elective isolated coronary artery bypass graft (CABG) procedure: control group (1 st January to 31 st December 2013), N =475; intervention group (1 st January to 31 st December 2014), N =428. Interventions: The intervention consisted of nasal application of OCT ointment three times daily, beginning on the day before surgery, and showering the night before and on the day of surgery with OCT soap. Results: A median sternotomy was performed in 805 (89.1%) patients and a minimally invasive direct coronary artery bypass procedure was performed in 98 (10.9%) patients. Overall, there was no difference in SSI rates between the control and intervention groups (15.4% vs 13.3%, P =0.39). The rate of harvest site SSIs was significantly lower in patients in the intervention group (2.5% vs 0.5%, P =0.01). Patients who had undergone a median sternotomy in the intervention group had a significantly lower rate of organ/space sternal SSIs (1.9% vs 0.3%, P =0.04). However, there was a trend towards an increased rate of deep incisional sternal SSIs (1.2% vs 2.9%, P =0.08). Multi-variate analysis did not identify a significant protective effect of the intervention (odds ratio 0.79, 95% confidence interval 0.53–1.15, P =0.27). Conclusions: Pre-operative decolonization with OCT did not reduce overall SSI rates in patients undergoing an elective isolated CABG procedure, but significantly decreased harvest site and organ/space sternal SSIs. Randomized controlled trials, including controlled patient adherence to the intervention, are required to confirm these observations and to determine the clinical utility of OCT in pre-operative decolonization.